The Artist as Monster : The Cinema of David Cronenberg - Beard, William, 1946- (Book collections on Project MUSE., 2006)
David Cronenberg is one of the most fascinating filmmakers in the world today. His provocative work has stimulated debate and received major retrospectives in museums, galleries, and cinematheques around the globe. This is the first book-length scholarly work in English on Cronenberg's films.